Équivalences - Éloy, Jean-Claude 1938-; Boulez, Pierre 1925-2016; Les Percussions de Strasbourg (France) (Paris Disques Adès, 1969)
'Impact de la musique contemporaine' was a series of lavishly designed 7" records under Gilbert Amy's direction of Le Domaine musical, a society founded by Pierre Boulez, Hermann Scherchen, and Jean-Louis Barrault.
Perforated record cover. Portrait of Éloy playing the piano on the record label.
Keywords: 20th Century (1901-2000); Percussion; Avant-garde